Determination of Critical Overload Transmission Line Using Novel Maximum Power Line Stability Index - Ali, A.; Ruhaizad, Ishak; Abdalla, Ahmed N. (Science Publishing Corporation, 2018)
Recent years, a larger number of DG’s are being employed especially at the critical load ends to reduce the burden on the main feeder. One of the benefits of employing DG that it improves the system voltage stability even with load increment. The primary focus of this paper rests on creating a novel line voltage stability index. The line stability index approach is proposed based on Thevenin theory to gauge the DG level impact on transmission line. Transmission issues due to the overloading of lines in high DG penetration areas during the outage scenarios taking place earlier. The rationale for the proposed strategy will be experimented on a standard IEEE 30 bus test system compared with other line voltage stability indexes.